KAJIAN SEMANTIK TUTURAN MOMBESARA PADA UPACARA ADAT PERKAWINAN SUKU TOLAKI - Alan, Alan (EDUTECH CONSULTANT, 2019)
The problem in this study is what meaning is contained in Mombesara's speech in the process of the Tolaki tribal marriage ceremony. This research is also expected to be useful for the development of knowledge in enhancing the ability to analyze and assess the function of the community at the Tolaki tribe wedding ceremony, this type of research is ethnographic qualitative research that directs efforts to a good understanding behind ideas, ideas, feelings of motives or beliefs. Specifically the research focuses on the meaning, function of an event, object, person, situation and condition of events, its relation to the context in the Mombesara traditional ceremony, Location of this study, Konawe Regency Wonggeduku Subdistrict. The subjects of this research are Tolea, Pabitara, Puutobu and Community Leaders which is deemed sufficient and mastering and understanding to provide the necessary information in accordance with research relating to the mombesara traditional ceremony.